2022
DOI: 10.3390/ijms23147836
|View full text |Cite
|
Sign up to set email alerts
|

T-Cell Intracellular Antigen 1-Like Protein in Physiology and Pathology

Abstract: T-cell intracellular antigen 1 (TIA1)-related/like (TIAR/TIAL1) protein is a multifunctional RNA-binding protein (RBP) involved in regulating many aspects of gene expression, independently or in combination with its paralog TIA1. TIAR was first described in 1992 by Paul Anderson’s lab in relation to the development of a cell death phenotype in immune system cells, as it possesses nucleolytic activity against cytotoxic lymphocyte target cells. Similar to TIA1, it is characterized by a subcellular nucleo-cytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 169 publications
(350 reference statements)
0
7
0
Order By: Relevance
“…At the same time, how mRNA degradation stimulated by CoV2 or SARS Nsp1 results in nuclear accumulation of TIAR is less clear. TIAR is an RNA binding protein with 3 RNA recognition motifs (RRM1-3) and an auxiliary C-terminal domain that is involved in many stages of the mRNA life cycle, from transcription and splicing to translation and stability [ 83 ]. It was shown that nuclear import of TIAR is dependent on transcription of new pre-mRNAs and requires ATP hydrolysis and the RRM2 RNA-binding activity, and that the inhibition of RNA synthesis by ActD causes egress of TIAR from the nucleus into the cytoplasm [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, how mRNA degradation stimulated by CoV2 or SARS Nsp1 results in nuclear accumulation of TIAR is less clear. TIAR is an RNA binding protein with 3 RNA recognition motifs (RRM1-3) and an auxiliary C-terminal domain that is involved in many stages of the mRNA life cycle, from transcription and splicing to translation and stability [ 83 ]. It was shown that nuclear import of TIAR is dependent on transcription of new pre-mRNAs and requires ATP hydrolysis and the RRM2 RNA-binding activity, and that the inhibition of RNA synthesis by ActD causes egress of TIAR from the nucleus into the cytoplasm [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, keywords related to cytotoxicity, T-lymphocytes, viral infections (including Epstein–Barr Virus/herpesvirus 4) and immune response mechanisms are shared in the cluster, highlighting their importance in immune-related functions and surveillance and viral pathways. Collectively, these findings demonstrate that both proteins contribute to the regulation of cytotoxic T-lymphocytes, which are critical for immune responses against viruses and cancers [ 4 , 6 , 36 ], including lymphoma.…”
Section: Tia1- and Tiar-related Networking Analysismentioning
confidence: 99%
“…In the case of TIAR, its involvement has been reported in inflammation, embryogenesis, carcinogenesis and neurodegenerative diseases such as neurofibromatosis type I, axon regeneration and Alzheimer’s disease [ 6 ].…”
Section: Implications Of Tia1 and Tiar In Human Pathologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, WNV produces its own RNA using TIA proteins. Furthermore, it is well known that Tick-borne encephalitis virus (TBEV) binds to viral replication sites via TIA-1 to regulate viral replication independently of the formation of stress granules (SGs) [37].…”
Section: Analysis Of the First Motif (Red Motif)mentioning
confidence: 99%